Content-specific differences in Padlet perception for collaborative learning amongst undergraduate students - Kosha J. Mehta; Isabelle Miletich; Michael Detyna (Association for Learning Technology, 2021)
Collaborative learning offers benefits but there is insufficient information on how students perceive specific digital tools supporting collaborative learning and whether there are content-related differences in students' perceptions. Here, we utilised Padlet to mediate collaborative learning amongst undergraduate students from two distinct disciplines, Dentistry and Bioscience to examine students' perceptions of Padlet-mediated learning and identify any content-specific differences. Data distribution was assessed via Shapiro-Wilk test, Mann-Whitney U test was used to assess distribution of responses and correlations were studied via Spearman's rank correlation coefficient (ρ). Data revealed that majority of students across both cohorts perceived Padlet as easy to use and beneficial to learning. Dentistry students perceived Padlet to be more beneficial to learning and easier to use than Bioscience students (p < 0.01). Most Bioscience students liked to undertake collaborative learning via Padlet, whereas most Dentistry students felt more confident to ask questions and better understood content via Padlet. In the Bioscience cohort, perceived benefit-to-learning strongly correlated (ρ = 0.75; p < 0.01) with fondness to use Padlet, whereas in the Dentistry cohort, it moderately correlated (ρ = 0.5; p < 0.01) with better understanding of subject content. Thematic analysis of students' textual responses revealed anonymity, peer-learning and engagement as key benefits. Thus, this study strengthened the evidence for using Padlet for collaborative learning in a wider context. Moreover, it uncovered significant disparities in students' perceptions of the tool, when used to foster learning of different subject contents.